2022
DOI: 10.1021/acs.jpcc.2c07107
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Abnormal Electrical Transport Transition from Pure Electronic to Mixed Ionic–Electronic in Multiferroic BiFeO3 Ceramics

Abstract: Pressure-induced structural changes could induce changes in transport properties and lead to a better understanding of the structure−property relationship. The evolution of the carrier transport properties of BiFeO 3 (BFO) ceramics under a high pressure was investigated through impedance spectroscopy measurements at room temperature combined with first-principles calculations. A pressure-induced abnormal transition from pure electronic to mixed ionic−electronic was found in the BFO ceramics Cmmm and Pnma phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…As the key variable in thermodynamics, hydrostatic pressure has been extensively used to nondestructively modulate the lattice structure and further tune the physical properties of functional nanomaterials, 35 such as enhanced superconductivity, 36 abnormal transport behavior, 37 and magnetic phase transitions. 38,39 It has been reported that bulk t-FeTe exhibits rich structural transitions under pressure, 16,40−42 and various anomalies of its electrical resistance appear with increasing pressure, partly due to the strongly entangled structural and electronic transitions that occur.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As the key variable in thermodynamics, hydrostatic pressure has been extensively used to nondestructively modulate the lattice structure and further tune the physical properties of functional nanomaterials, 35 such as enhanced superconductivity, 36 abnormal transport behavior, 37 and magnetic phase transitions. 38,39 It has been reported that bulk t-FeTe exhibits rich structural transitions under pressure, 16,40−42 and various anomalies of its electrical resistance appear with increasing pressure, partly due to the strongly entangled structural and electronic transitions that occur.…”
mentioning
confidence: 99%
“…As the key variable in thermodynamics, hydrostatic pressure has been extensively used to nondestructively modulate the lattice structure and further tune the physical properties of functional nanomaterials, such as enhanced superconductivity, abnormal transport behavior, and magnetic phase transitions. , It has been reported that bulk t -FeTe exhibits rich structural transitions under pressure, ,− and various anomalies of its electrical resistance appear with increasing pressure, partly due to the strongly entangled structural and electronic transitions that occur. , Meanwhile, magnetic studies of t -FeTe under hydrostatic pressure immaturely suggest the magnetic transition from low-pressure AFM order to high-pressure FM order. ,, Moreover, the experimental exploration of the electrical transport, structure, and magnetism of h -FeTe under high pressure is still sparse. 2D crystalline FeTe with tunable phases as well as magnetism is extremely rare in the TMD family. , 2D t -FeTe and h -FeTe nanosheets have an identical chemical composition yet reflect distinct lattice structures and magnetic properties, which provides us a desirable platform to explore their symmetry–magnetism correlation and even to potentially unravel the attractive mechanism in iron-based superconductors.…”
mentioning
confidence: 99%